1998
DOI: 10.1074/jbc.273.44.28868
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-independent Activation of Atrial Muscarinic Potassium Channels in the Absence of Nucleotides

Abstract: The removal of nucleotides from the solution bathing the inner face of excised patches of frog atrial membranes was found to activate muscarinic K ؉ channels in the absence of agonists. Channel activation was also observed in Mg 2؉-free solutions and blocked by low (0.1-10 M) concentrations of GDP or GTP. After full activation was achieved, channel openings were abolished by the application of GDP-bound G␣ i2 but were not affected by exogenous G␤␥ dimers, suggesting that effector activation is a consequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…(6) After complete rundown of ATP‐sensitive K + channels, a process that has been attributed to depletion of PIP/PIP 2 in the membrane (Hilgemann & Ball, 1996; Fan & Makielski, 1997), we could easily activate K ACh channels with GTP (with ACh in the pipette) or GTPγS. In support of this, it was reported recently that K ACh channels could be activated via G protein even in the complete absence of ATP and Na + (Otero et al 1998). Together, these observations suggest strongly that ATP and PIP/PIP 2 use separate signalling pathways to modulate the G protein‐gated K + channel.…”
Section: Discussionsupporting
confidence: 55%
“…(6) After complete rundown of ATP‐sensitive K + channels, a process that has been attributed to depletion of PIP/PIP 2 in the membrane (Hilgemann & Ball, 1996; Fan & Makielski, 1997), we could easily activate K ACh channels with GTP (with ACh in the pipette) or GTPγS. In support of this, it was reported recently that K ACh channels could be activated via G protein even in the complete absence of ATP and Na + (Otero et al 1998). Together, these observations suggest strongly that ATP and PIP/PIP 2 use separate signalling pathways to modulate the G protein‐gated K + channel.…”
Section: Discussionsupporting
confidence: 55%
“…This channel activation was blocked upon addition of GDP and GDP-bound G αi2 (Otero et al 1998). The authors concluded that the nucleotide-free form of G proteins has some of the characteristics of the GTP-bound, activated form.…”
Section: Discussionmentioning
confidence: 98%
“…2). Spontaneous run‐up of K ACh activity in nucleotide‐free solutions has also been reported for excised patches from frog atrial myocytes at 20°C (Otero et al 1998). In those experiments, the increase in activity was much smaller ( NP o < 0.05) than we observed in excised patches from guinea‐pig myocytes at 35°C and was attributed to spontaneous release of βγ subunits.…”
Section: Discussionmentioning
confidence: 73%